Efficacy of Ondansetron used Prophylactically during Spinal Anesthesia for Elective Caesarean Section - Anumta Shahab Chaudary, Ramesha Ali, Aqsa Tariq, Ali Bin Tariq, Rifah Zia, Iqra Toor (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To record the efficacy of ondansetron used prophylactically during spinal anesthesia for elective caesarean section. Methodology: During July to December 2022, this study was conducted by using randomized control trial method at Department of Anesthesia of Jinnah Hospital, Lahore, the enrolled 120 cases were those with ASA II and already scheduled to perform cesarean delivery electively and using spinal anesthesia. To know the efficacy of Ondansetron, we divided the participants in Group O and P equally. Intravenous ondansetron was administered in Group O with the dose 0.1 mg/kg, well diluted in 5ml distilled water, whereas our control group receiving 5 ml of normal saline was allotted Group P, in both group Ondansetron and N/S was administered before intrathecal injection. Preloading was performed using Ringer’s lactate at 10 ml/kg through an 18G intravenous cannula over 10 minutes. Spinal anesthesia was performed in the sitting position at the L3–L4 interspace using a 25-gauge Quincke needle. A total of 1.5 ml of 0.75% hyperbaric bupivacaine was administered into the subarachnoid space. Patients were then positioned supine with a 15° left lateral tilt to reduce aortocaval compression and optimize cephalad drug spread. Sensory blockade was evaluated using a pinprick test prior to incision. Oxygen was supplemented at 3 L/min via face mask throughout the procedure. By using definition of hypotension “a decrease in mean arterial pressure exceeding 25% from baseline or an absolute MAP <60 mmHg” management included intravenous phenylephrine (50–100 µg) or ephedrine, as appropriate. A heart rate under 50 beats per minute, indicative of bradycardia often associated with hypotension, was treated using 0.5 mg of atropine intravenously. Results: In the ondansetron group we recorded (33.3%) cases of hypotension and (73.3%) in placebo, showing remarkable reduced hypotensive effect with (p = 0.00011) in Ondansetron group. Conclusion: Women with intravenous administration of ondansetron as prophylactically recorded with decreased findings of hypotension as compared to those with normal saline. Keywords: Elective caesarean section, ondansetron, placebo, hypotension.